Trade Policy, Income Risk, and Welfare - Krebs, Tom; Krishna, Pravin; Maloney, William (The Review of Economics and Statistics, 2010)
This paper develops a framework to study empirically the relationship between trade policy and individual income risk and to evaluate the associated welfare consequences. The analysis proceeds in three steps. First, longitudinal data on workers are used to estimate time-varying individual income risk parameters in various manufacturing sectors. Second, the estimated income risk parameters and data on trade barriers are used to analyze the relationship between trade policy and income risk. Finally, a simple dynamic incomplete-market model is used to assess the corresponding welfare costs. In the implementation of this methodology using Mexican data, we find that trade policy changes have a significant short-run effect on income risk. Further, while the tariff level has an insignificant mean effect, it nevertheless changes the degree to which macroeconomic shocks affect income risk.